Implementasi Nilai-Nilai Tasawuf dalam Pelaksanaan Hipnoterapi Pada Komunitas Hipnosis Cirebon (KHC) - Asiyah, Siti; Makarrim, Alfiyah (IAIN Manado, 2025)
This study aims to explore the implementation of Sufi values in hypnotherapy practices carried out by the Hypnosis Community of Cirebon (KHC). Using a qualitative research method with a case study approach, this research investigates how Sufi principles such as tawakal, sabar, syukur, and husnuzan are integrated into various stages of hypnotherapy, from pre-induction to post-hypnotic suggestion. Data were collected through participatory observation, in-depth interviews, and documentation, involving KHC therapists and clients. The results reveal that the incorporation of Sufi values enhances the therapeutic process, creating a holistic healing experience that aligns with the spiritual beliefs of clients. This integration also provides a new perspective on alternative therapy practices that bridge psychological and spiritual dimensions. The study concludes that the application of Sufisme values in hypnotherapy not only supports mental health treatment but also enriches the interdisciplinary discourse between Tasawuf and psychotherapy.